Smart Web-Based Kos Management dengan Automated Reminder menggunakan Metode Waterfall - Fahmil Ulum; Aang Alim Murtopo; Syefudin Syefudin (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The rapid development of digital technology has encouraged various activities that were previously carried out manually to shift toward digital-based systems, including boarding house management. However, in practice, many boarding house owners still manage tenant records, payment transactions, and room management manually, which often leads to problems such as unorganized data, recording errors, and payment delays that are difficult to monitor. This condition results in low operational efficiency and limited access to information for boarding house owners. This study aims to design and develop a web-based boarding house management information system that can facilitate more structured, accurate, and efficient data management. The developed system is equipped with features for managing tenant data, room data, payment transaction records, payment status monitoring, and automatic reminder notifications through the WhatsApp Gateway to address payment delays. The research method used is software engineering with the Waterfall development model, which consists of the stages of analysis, design, implementation, and testing. Data collection techniques were conducted through observation, interviews, and literature studies. The results of testing using the black-box testing method showed that all system features, including payment management, tenant data management, and WhatsApp Gateway notifications, functioned according to their intended purposes. The black-box testing results indicated that 95% of the features functioned according to the specified requirements.